2015
DOI: 10.1109/jphot.2015.2415672
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tensile Strain on Optical Anisotropy and Exciton of <inline-formula> <tex-math notation="TeX">$m$</tex-math></inline-formula>-Plane ZnO

Abstract: The near band edge emission of the tensile-strained m-plane ZnO film grown on (112)LaAlO 3 substrates shows abnormal low polarization degree ( ¼ 0:1). The temperature dependency of polarization degree clarifies the origins of different emission peaks. In tensile-strained m-plane ZnO, the [0001] polarized state is upper shifted and is overlapping with the [1120] polarized state. This phenomenon causes the abnormal low polarization degree and reveals the effect of strain on the emission anisotropy of m-plane ZnO. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It is found that, unlike graphene, topological insulators have a non‐zero bandgap and large modulation depth (up to 95%), which are more conducive to the development of mode‐locked lasers. In view of these advantages, various mode‐locked fiber lasers based on topological insulators including Bi 2 Se 3 , Bi 2 Te 3 , Sb 2 Te 3 , have been developed, as shown in Table . Through these efforts, some exciting results such as maximum repetition rate, maximum output power, and minimum pulse width of 3.125 GHz, 45.3 mW, and 195 fs have been obtained, respectively.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…It is found that, unlike graphene, topological insulators have a non‐zero bandgap and large modulation depth (up to 95%), which are more conducive to the development of mode‐locked lasers. In view of these advantages, various mode‐locked fiber lasers based on topological insulators including Bi 2 Se 3 , Bi 2 Te 3 , Sb 2 Te 3 , have been developed, as shown in Table . Through these efforts, some exciting results such as maximum repetition rate, maximum output power, and minimum pulse width of 3.125 GHz, 45.3 mW, and 195 fs have been obtained, respectively.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…Concentric circular focusing grating couplers have been known since a long time and they have been implemented as optical routing, for example, for wavelength division multiplexing (as illustrated in Figure g), for cavity resonators, or for quantum information processing . Recent optimizations include circular RWGs on a membrane, apodized focusing grating couplers (sketched in Figure a), and long working distance gratings . A focusing spatial bandpass transmission filter based on a periodic RWG was also reported with a multilayer geometry allowing broadband reflection sidebands .…”
Section: Effects Associated With Rwgsmentioning
confidence: 99%
“…The DOP for luminescence of nonpolar ZnO was, however, affected strongly by the magnitude and direction of the in-plane strains [7][8][9]15]. The polarization was improved with the compressive lattice strains in a-plane [2,5] and m-plane ZnO [8] compared to a strain-free layer.…”
Section: Introductionmentioning
confidence: 95%
“…On the contrary, the large DOP was ascribed to the small in-plane strains [16] or enhanced strain relaxation [7] in a-plane ZnO. It is interesting that the tensile strain leads to an abnormally low polarization in m-plane ZnO [9]. Except for the lattice strain, large polarization was also attributed to the small striped domain structure in a-plane ZnO grown at low temperature [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation